Gamma rays as an innovative tool for synthesizing conducting copolymers with improved properties. (7th July 2021) - Bahry, Teseer; Khurshid, Benazir; Chouli, Yamina; Abou Zeid, Souad; Sollogoub, Cyrille; Gervais, Matthieu; Bui, Thanh-Tuân; Goubard, Fabrice; Remita, Samy
Abstract : Radiation chemistry was used as an alternative methodology for synthesizing conducting copolymers in water and dichloromethane. Abstract : In the present study, copolymers of pyrrole (Py) with different co-monomers (thiophene derivatives) were originally polymerized through two radiolytic approaches: water radiolysis and dichloromethane radiolysis. This method can be easily controlled and is adaptable. The main objective of copolymerization is to increase the solubility and processability of polypyrrole (PPy). The synthesis of copolymers was validated by UV-Vis absorption spectroscopy that indicates monomers' quantitative consumption and by ATR-FTIR that validates their chemical composition. Scanning electron microscopy (SEM) and cryogenic transmission electron microscopy (Cryo-TEM) were used to check the morphology and topography of the synthesized copolymers of Py and to compare them with their respective homopolymers. Additionally, a comparative study of thermal behavior and molecular weight distribution of copolymers with their homopolymers was performed using thermogravimetric analysis (TGA) and size exclusion chromatography (SEC), respectively. Finally, conductivity and electrochemical measurements were performed. The results showed the successful synthesis of copolymers of Py by this novel radiolytic method with changes in their morphologies and physicochemical properties with respect to the homopolymers. The present work definitely validates radiation chemistry as an alternative approach to synthesize conducting copolymers.